Climate Change and Stock Market Performance in Nigeria - Olurin, Olurotimi; Oladipo, Samson Idowu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study investigates the impact of climate change variables including carbon emissions, rainfall, temperature, inflation, real interest rates, Foreign Direct Investment, and Gross Domestic Product per capita growth rate on stock market performance in Nigeria using the Autoregressive Distributed Lag (ARDL) bound testing approach. Annual data from 1990 to 2022 was analyzed to explore both long-run and short-run dynamics. The results reveal that in the long run carbon emissions and foreign direct investment have a positive and significant effect on stock performance, while inflation has a significantly negative effect. Conversely, in the short run, lag one carbon emission and foreign direct investment one-year lag have a negative and significant effect on stock performance. However, rainfall and temperature did not show any significant effect both in the short and long run. The model demonstrates robust explanatory power, accounting for approximately 96% of the variation in stock market performance. These findings underscore the complex and nuanced interplay between climate change, macroeconomic variables, and financial markets, highlighting the need for policymakers, investors, and corporate managers to address climate and economic risks while leveraging potential opportunities in Nigeria’s evolving financial landscape.
Keywords: Climate Change; Stock Market Performance; Carbon Emission; Real Interest Rate; Auto-regressive Distributed Lag